2018
DOI: 10.1097/lgt.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cervical Cancer Screening in California's Family Planning Program

Abstract: Changes in screening interval guidelines are associated with overall decreased screening. This trend was strongest among women aged 21 to 24 years, even as they continued to be screened appropriately for chlamydia, suggesting many missed opportunities. Efforts to reduce unnecessary cervical cancer screening should be monitored to maintain appropriate screening rates to avoid advanced-stage diagnoses and higher health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Nonadherence to regular screening as individuals approach the age for cessation of screening 56 is of particular importance and may reduce the benefits. Failure to initiate screening near the recommended starting age may similarly reduce screening benefits 57 …”
Section: Methodsmentioning
confidence: 99%
“…Nonadherence to regular screening as individuals approach the age for cessation of screening 56 is of particular importance and may reduce the benefits. Failure to initiate screening near the recommended starting age may similarly reduce screening benefits 57 …”
Section: Methodsmentioning
confidence: 99%
“… 4 In addition, screening rates seem to be falling precipitously in this age group. 5 Therefore, arguments can be made for continuing to advocate screening among women aged 21 to 24 years so that they make cervical screening part of their normal well woman care and facilitate prevention of cancers among women aged 25 to 29 years related to underscreening. In this forum, we address the question of when to begin screening in the US, considering both the epidemiology and natural history of disease and the practical limitations of the US healthcare setting.…”
Section: Moderator Statementmentioning
confidence: 99%
“…11 There are now disturbing data that cervical cancer screening has been decreasing among all women, but specifically young women. 5 Although screening is recommended at 3-year intervals (36 months), a recent study using Family Pact claims that data showed that the percent of women aged 21 to 29 years having at least a single screen within 42 months decreased from approximately 75% in 2012 to less than 50% in 2015, 5 indicating that increasing the screening interval from 1 to 3 years has resulted in high rates of underscreening in women younger than 30 years. In contrast, screening rates for chlamydia did not change in women aged 20 to 24 years, suggesting that women continue to have contact with the health care system but are not receiving the recommended cervical cancer screening.…”
Section: Sidementioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians may therefore be less likely to adhere to recommended lengthier screening intervals due to concerns about patients' perceptions or their own beliefs. The implementation of less frequent testing intervals and less invasive follow up of abnormal cervical cytology results is complicated by the fact that some population groups have inadequate screening rates even with the new guidelines (at least one Pap test in the past three years) which continues the development of tools that aim to increase cervical cancer testing [14][15][16].…”
Section: Introductionmentioning
confidence: 99%